Oncoproteins E6 and E7 upregulate topoisomerase I to activate the cGAS-PD-L1 pathway in cervical cancer development - Luo, Ying; Niu, Mengda; Liu, Yanfei; Zhang, Miaochang; Deng, Yuanyuan; Mu, Dan; Xu, Junfen; Hong, Shiyuan (Frontiers in Pharmacology, 2024)
Cervical cancer (CC) ranks as the fourth most lethal cancer among women worldwide. The DNA damage repair (DDR) protein topoisomerase I (TOP1) plays a crucial role in maintaining genomic stability and has been implicated in various cancers. However, its specific functions and mechanisms in CC remain unclear. In this study, we found that TOP1 was highly expressed in cervical intraepithelial neoplasia (CIN) and CC tissues. Elevated TOP1 expression is negatively correlated with the prognosis of CC patients. Inhibition of TOP1 suppresses CC cell growth and impairs DNA repair both in vitro and in vivo. Furthermore, TOP1 is responsible for the production of programmed death-ligand 1 (PD-L1) in a cyclic GMP-AMP synthase (cGAS)-dependent manner. Silencing TOP1 reduces the expression of cGAS and PD-L1. Additionally, TOP1 co-localizes with cGAS in CC cells. Human papillomavirus oncoproteins E6 and E7 significantly upregulate TOP1 and activate the non-canonical cGAS-PD-L1 pathway to promote CC development. Our findings suggest that the TOP1-cGAS-PD-L1 signaling axis could be a promising therapeutic target for CC.